Implementasi Program Corporate Social Responsibility (CSR) di PT Brilian Elok Sukses Dalam Perspektif Ekonomi Islam - Lusiyaningsih; Hamdani, Ikhwan; Hakiem, Hilman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Corporate Social Responsibility is a social and environmental responsibility for companies that can be a solution in overcoming existing problems, such as environmental damage and the distance between people's economic levels that occur in an area. In Islam itself, CSR is a consequence that must be applied in conducting business, so that it is in accordance with the objectives of Islamic law, namely maslahat (maqashid al syai'ah). But in reality there are still few companies that implement the CSR program. This research was conducted with the aim of knowing how the implementation of the CSR program at PT Brilian Elok Sukses, as well as the suitability of the program in the view of Islamic economics. In this study, researchers used qualitative methods by conducting observations, interviews, and documentation to collect field data and apply empirical law, the aim is to strengthen the research. The results of the study show that the company has implemented the SCR program with funds obtained from income on November 11 each year which is commemorated as the anniversary of the company, distribution of funds divided by 60% for orphans and the poor, 20% for social activities and 20% for scholarships. Distribution is carried out directly by the company given to the company's environmental area. Then for the suitability of CSR in Islam it is analyzed through elements such as Al Adl and Al Ihsan and the distribution is carried out in the form of infaq and Sadaqah. Keywords: CSR, maqashid al syai’ah.